The Relation Between Diabetes Self-Efficacy and Psychological Distress Among Older Adults: Do Racial and Ethnic Differences Exist?. (March 2015) - Kim, Giyeon; Shim, Ruth; Ford, Katy L.; Baker, Tamara A.
Objective: This study examined racial/ethnic differences in the relationship between diabetes self-efficacy and psychological distress among older adults with diabetes mellitus.Method: Adults aged 60 or older with a diagnosis of diabetes mellitus ( N = 3, 067) were drawn from the 2009 California Health Interview Survey (CHIS). Hierarchical multiple regression analyses were conducted.Results: After controlling for covariates, African Americans and those with higher levels of diabetes self-efficacy tended to have lower levels of psychological distress. Significant interactions were found in the Hispanic/Latino and Asian groups: The effect of diabetes self-efficacy on psychological distress was greater for Hispanics/Latinos and Asians than non-Hispanic Whites.Discussion: Findings suggest that diabetes self-efficacy is associated with psychological distress among older diabetic patients and that race/ethnicity moderates the relationship between diabetes self-efficacy and psychological distress. Increasing diabetes self-efficacy will help racial/ethnic minority older patients with diabetes to improve psychological well-being at a greater level.